A guide to Whittle maximum likelihood estimator in MATLAB - Roume, Clément (Frontiers in Network Physiology, 2023)
The assessment of physiological complexity, via the estimation of monofractal exponents or multifractal spectra of biological signals, is a recent field of research that allows for detecting relevant and original information for health, learning or autonomy preservation. This tutorial aims at introducing Whittle maximum likelihood estimator that estimates the monofractal exponent of time series. After introducing Whittle maximum likelihood estimator and presenting each of the steps leading to the construction of the algorithm, this tutorial discusses the performance of this estimator by comparing it to widely used detrended fluctuation analysis (DFA). The objective of this tutorial is to propose to the reader an alternative monofractal estimation method, which is simple to implement, and whose high accuracy allows the analysis of shorter time series than those classically used with other monofractal analysis methods.